Hakikat Pendidikan Tinggi Islam Negeri dan Swasta: Kajian Filsafat Pendidikan Barat dan Islam - Miswanto Miswanto (STIT Fatahillah, 2026)
Islamic Higher Education (PTI), both state and private, plays a strategic role in developing intellectually, spiritually, and morally superior Muslim human resources. However, the differences in institutional status between State Islamic Religious Higher Education Institutions (PTKIN) and Private Islamic Religious Higher Education Institutions (PTKIS) often give rise to differences in philosophical orientations, paradigms, and educational practices. This study aims to analyze the nature of state and private Islamic higher education from the perspective of Western and Islamic educational philosophies, identify common ground and philosophical differences between the two, and formulate philosophical implications for the development of an integrative and value-oriented paradigm for Islamic higher education. This study uses a qualitative approach with library research on relevant classical and contemporary literature. Data were analyzed using content analysis techniques and a comparative-philosophical approach. The results show that Islamic higher education exists in a dialogue between modern rationality developed in Western educational philosophy and the transcendental values ​​that are at the core of Islamic educational philosophy. The differences between PTKIN and PTKIS are more implementative and managerial in nature, rather than in their underlying philosophical objectives. This research emphasizes the importance of developing an integrative paradigm of Islamic higher education to maintain academic relevance while strengthening the epistemological and axiological identity of Islamic education amidst global challenges.